Author Correction: A comprehensive map coupling histone modifications with gene regulation in adult dopaminergic and serotonergic neurons. Issue 1 (December 2018) - Södersten, Erik; Toskas, Konstantinos; Rraklli, Vilma; Tiklova, Katarina; Björklund, Åsa; Ringnér, Markus; Perlmann, Thomas; Holmberg, Johan
In the originally published version of this Article, financial support was not fully acknowledged. The PDF and HTML versions of the Article have now been corrected to include support to Thomas Perlmann provided by Knut and Alice Wallenberg Foundation (grant 2013.0075) and Swedish Research Council (VR; grant 2016-02506).